CADASIL: two new cases with intracerebral hemorrhage. Issue 4 (7th March 2017) - Zhang, Chen; Li, Wei; Li, Shaowu; Niu, Songtao; Wang, Xingao; Tang, Hefei; Yu, Xueying; Chen, Bin; Shi, Yuzhi; Chen, Qihua; Guo, Liying; Pan, Yunzhu; et al.
Abstract: Whether cerebral autosomal‐dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a risk factor for spontaneous intracerebral hemorrhage (ICH) and influences outcomes remains unclear. In this study, we report two cases of CADASIL presenting with cerebral hemorrhages. These cases suggest that a CADASIL vasculopathy by itself mainly results in ICH, as indicated by slight vascular risk factors and prominent neuroimaging abnormalities, suggesting that CADASIL should be considered a risk factor for ICH. Interestingly, decreased perihematomal edema was noted in ICH patients with CADASIL in this study.